Travel guide on Palm Hotel Room Reservation System (TgoP- HRRS) / Wong Pak Liang - Wong, Pak Liang (2001)
Since the released of the Pilot 1000 by Palm Computing in 1996, the Pilot's market grew faster than any other computing product in history. As an extension of desktop system, this handheld computing device allows users to view and enter small amounts of data while away from the desktop. In Malaysia, they are a lot of website, which provide information m travel. However, from the study we have done, there is no significant number shown that any of the website provide service on Palm. This study has bring us the idea to develop a website or more accurately a web clipping solution for the travel guide around Klang Valley on Palm, Travel Guide on Palm (TGoP). The TGoP is divided into two subsystems, which are Information Sub System and Hotel Room Reservation System. This report focuses on the Hotel Room Reservation System (HRRS). The HRRS provides an online room reservation service which mainly focus on the Palm users. The users may retrieve hotel information from the HRRS and makes a reservation via the wireless network. The HRRS development is divided into four parts, which are client section, portal administrator section, hotel administrator section and officer section. The client is the person who be serviced. The portal administrator maintains the HRRS to make sure the services are available at any time. The hotel administrator control the officer to make sure the room reservation service is offered all the time. The successful of the TGoP HRRS will widen the usage of the Palm OS device and at the same time encourage the tourism industry in Malaysia.